2016
DOI: 10.1177/1591019916637360
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative catheter spinal angiography and embolization of cervical spinal tumors: Outcomes from a single center

Abstract: Objective The existing literature regarding preoperative cervical spinal tumor embolization is sparse, with few discussions on the indications, risks, and best techniques. We present our experience with the preoperative endovascular management of hypervascular cervical spinal tumors. Methods We performed a retrospective review of all patients who underwent preoperative spinal angiography (regardless of whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…A compliant balloon is inflated at the level of possible occlusion for at least 20 minutes, During the BTO, the competence of contralateral vertebral and carotid arteries as well as serial neurological examinations should be performed. 18,19 Patsalides et al reported vertebral artery occlusion was successfully performed in 40.1% (N ¼ 20) of embolization procedures, without any neurological complications. 19…”
Section: Balloon Test Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A compliant balloon is inflated at the level of possible occlusion for at least 20 minutes, During the BTO, the competence of contralateral vertebral and carotid arteries as well as serial neurological examinations should be performed. 18,19 Patsalides et al reported vertebral artery occlusion was successfully performed in 40.1% (N ¼ 20) of embolization procedures, without any neurological complications. 19…”
Section: Balloon Test Occlusionmentioning
confidence: 99%
“…18,19 Patsalides et al reported vertebral artery occlusion was successfully performed in 40.1% (N ¼ 20) of embolization procedures, without any neurological complications. 19…”
Section: Balloon Test Occlusionmentioning
confidence: 99%
“…Preoperative embolization has been shown to provide better visibility for the surgeon, shorten operative time, reduce intraoperative blood loss while assisting tumor resection [ 16 , 17 ]. Additionally, preoperative embolization has also been shown to reduce intraoperative blood loss in the treatment of vascular cervical spine tumors and osseous metastasis [ 2 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Onyx was used in this case as its non-adhesive nature provided slower, intermittent and controlled injection, minimizing the potential risk of unintentional embolic material traveling into anastomotic vessels. In this case, bilateral occipital arteries are the major contributors of tumor vascularity and potential anastomosis into the VA and the stylomastoid branch need to be carefully monitored [ 18 , 19 ]. Partial embolization has been shown to reduce operative blood loss and in this case was performed as a palliative measure to mitigate blood loss during resection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation